Reinforced Ni(ii)-cyclam derivatives as dual H-1/F-19 MRI probes - Pujales Paradela, Rosa; et al. (Chemical Communications, 2019)
Reinforced cross-bridged Ni2+-cyclam complexes were functionalised with pendant arms containing both amide protons and CF3 groups that lead to a dual H-1/F-19 response. The resulting complexes possess very high inertness favourable for MRI applications. The paramagnetism of the Ni2+ ion shifts the amide resonance 56 ppm away from bulk water favouring the chemical exchange saturation transfer (CEST) effect and shortening the acquisition times in F-19 magnetic resonance imaging (MRI) experiments, thus enhancing the signal-to-noise ratios compared to the fluorinated diamagnetic reference.